2020
DOI: 10.7759/cureus.10020
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immunoglobulin-Associated Elevation of Liver Enzymes in Neurological Autoimmune Disorder: A Case Series

Abstract: Intravenous immunoglobulin (IVIG) is used in the treatment of a variety of autoimmune neurological disorders and is generally regarded as safe. We present a case series where IVIG causes transaminitis. The adverse effects are mostly due to the stabilizing agent used to prepare the IVIG (e.g., maltose in this series). While the adverse effects are usually self-limiting, physicians should be cautious in administering an IVIG preparation to these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
7
1
Order By: Relevance
“…Elevated LFTs, hyperbilirubinemia, and subsequent biopsy consistent with drug-induced hepatitis were attributed to the increased dose of IVIG that may cause transaminitis ( 17 ); consequently, the subsequent dose of IVIG was reduced. This observation emphasizes the importance of a multidisciplinary team approach for such a unique presentation, which was a strength of our case.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated LFTs, hyperbilirubinemia, and subsequent biopsy consistent with drug-induced hepatitis were attributed to the increased dose of IVIG that may cause transaminitis ( 17 ); consequently, the subsequent dose of IVIG was reduced. This observation emphasizes the importance of a multidisciplinary team approach for such a unique presentation, which was a strength of our case.…”
Section: Discussionmentioning
confidence: 99%
“…Gammagard liquid, which was the IVIG formulation used in our patient, contains glycine and is not known to cause elevated liver enzymes. 4,5 In our case, it was important to rule out other causes of liver injury.…”
Section: Discussionmentioning
confidence: 90%
“…A recent retrospective cohort study ( n = 104) found that high serum total protein levels in paediatric neurological patients were significantly associated with the occurrence of IVIg-ARs (OR, 14.8; 95% confidence interval, 2.4–90.5; p < 0.01) [17]. A reversible, asymptomatic rise in liver enzymes, particularly transaminase levels is also common with IVIg administration [20, 23, 26, 39, 44, 69].…”
Section: Abnormalities Of Laboratory Parametersmentioning
confidence: 99%
“…Sugar-stabilised IVIg formula may be associated with eczematous skin reactions – this AR was the main reason for discontinuation (58%) of this product in the study [18]. A prospective case series suggested that maltose-containing stabilising agents in IVIg preparations may cause a self-limited, asymptomatic transaminitis [69]. One prospective cohort study also found the occurrence of transaminitis to be associated with sucrose and PEG/sorbitol-containing IVIg preparations as opposed to glycine-containing preparations; the underlying mechanism was unclear [26].…”
Section: Treatment-specific Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation